2002
DOI: 10.1080/1606635021000034030
|View full text |Cite
|
Sign up to set email alerts
|

The Close Relatives of Untreated Heavy Drinkers: Perspectives on Heavy Drinking and its Effects

Abstract: Aims. To describe the positions adopted by close family members of a community sample of untreated heavy drinkers. Design. Detailed interview and questionnaire study of a sample of close family members and the heavy drinkers to whom they were related. Sample. 50 close relatives of 50 heavy drinkers drawn from a community cohort of 500 in the English West Midlands. Data. Perceived benefits and drawbacks of drinking checklist (family members and heavy drinkers); readiness to change questionnaire (family members … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…These findings are consistent with socio-emotional selectivity theory, which posits that older individuals are motivated to maintain good interpersonal relationships, in part because they are aware of the relatively short life span remaining to them [4548]. Moreover, some husbands and wives point to positive aspects of their family members’ moderate to heavy drinking, including benefits for the marital relationship and social life [49]. …”
Section: Discussionsupporting
confidence: 81%
“…These findings are consistent with socio-emotional selectivity theory, which posits that older individuals are motivated to maintain good interpersonal relationships, in part because they are aware of the relatively short life span remaining to them [4548]. Moreover, some husbands and wives point to positive aspects of their family members’ moderate to heavy drinking, including benefits for the marital relationship and social life [49]. …”
Section: Discussionsupporting
confidence: 81%
“…It bears mentioning that in this era of evolving family forms, extended family members are also affected by substance abuse. There appears to be some evidence that extended family members, or second-degree relatives, both impact the nuclear family through substance abuse and are similarly impacted by substance abuse in the nuclear family (Orford, Dalton, Hartney, Ferrins-Brown, Kerr, & Maslin, 2002;Ragin, Pilotti, Madry, Sage, Bingham, & Primm, 2002).…”
Section: Impact Of Substance Abuse On Children and Familiesmentioning
confidence: 95%
“…The age of participants was limited to the range of 25-55 years. The sample was reasonably representative of the British population in terms of socio-economic status (Orford et al, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…The pub as a location for drinking appeared to be important for members of the BUHD cohort. At Wave 1, in 1997, data from a one-week timeline follow-back (Sobell & Sobell, 1996) suggested that 42% of the cohort were predominantly drinking in pubs or other licensed premises (Orford, Dalton, Hartney, Ferrins-Brown, Kerr, & Maslin, 1998). Nearly all of the sample drank in a pub from time to time.…”
Section: Introductionmentioning
confidence: 98%